Pseudomembranous enterocolitis complicating ampicillin therapy. Issue 620 (June 1977) - Read, L.; Cove-Smith, J. R.
Abstract : A case of fatal pseudomembranous enterocolitis associated with ampicillin therapy is described and possible mechanisms for its production discussed.